2007
DOI: 10.1016/j.joca.2006.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of IGF-1 and OP-1 on matrix formation by normal and OA chondrocytes cultured in alginate beads

Abstract: The results obtained in the current study suggest that combined therapy with IGF-1 and OP-1 may have a greater potential in treating cartilage defects seen in OA than use of either growth factor alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 47 publications
6
73
1
Order By: Relevance
“…Despite the diminished ability of IGF-I to decrease catabolism in aged and OA cartilage, studies suggest that a combination of IGF-I and BMP-7 results in greater repair potential than either growth factor alone [15,54]. These studies demonstrated that in general, BMP-7 was more potent than IGF-I in stimulating matrix synthesis in aged and OA cells, but the greatest increase in matrix synthesis was observed after combination treatment with BMP-7 and IGF-I.…”
Section: Insulin-like Growth Factor-imentioning
confidence: 99%
“…Despite the diminished ability of IGF-I to decrease catabolism in aged and OA cartilage, studies suggest that a combination of IGF-I and BMP-7 results in greater repair potential than either growth factor alone [15,54]. These studies demonstrated that in general, BMP-7 was more potent than IGF-I in stimulating matrix synthesis in aged and OA cells, but the greatest increase in matrix synthesis was observed after combination treatment with BMP-7 and IGF-I.…”
Section: Insulin-like Growth Factor-imentioning
confidence: 99%
“…Interleukin-1 receptor antagonist protein (IL-1Ra) can inhibit cartilage matrix degeneration by blocking the adverse effects of interleukin-1 (IL-1) in OA (Frisbie et al, 2002). Insulin-like growth factor-1 (IGF-1) promotes the synthesis of cartilage matrix (Chubinskaya et al, 2007). These results show that bFGF, IL-1Ra and IGF-1 are potential candidate cytokines in gene therapy of OA.…”
Section: Introductionmentioning
confidence: 99%
“…4) For example, BMP-7, a member of transforming growth factor-β (TGF-β)/BMP superfamily, is a representative anabolic growth factor to repair the articular cartilage through the stimulation of cartilage-specific extracellular proteins such as collagen type II, aggrecan, decorin, fibronectin and hyaluronan. [23][24][25] Recently, Hunter et al, performed the phase 1 safety and tolerability study of BMP-7 in symptomatic knee OA and reported that patients received the BMP-7 were a trend toward symptomatic improvement without toxicity.…”
Section: Discussionmentioning
confidence: 99%